A Variant of COL3A1 (rs3134646) Is Associated With Risk of Developing Diverticulosis in White Men. Issue 5 (May 2018) - Reichert, Matthias Christian; Kupcinskas, Juozas; Krawczyk, Marcin; Jüngst, Christoph; Casper, Markus; Grünhage, Frank; Appenrodt, Beate; Zimmer, Vincent; Weber, Susanne Nicole; Tamelis, Algimantas; Lukosiene, Jaune Ieva; Pauziene, Neringa; et al.
Abstract : BACKGROUND: Colonic diverticulosis is one of the most common gastroenterological disorders. Although diverticulosis is typically benign, many individuals develop diverticulitis or other aspects of diverticular disease. Diverticulosis is thought to stem from a complex interaction of environmental, dietary, and genetic factors; however, the contributing genetic factors remain unknown. OBJECTIVE: The aim of our present study was to determine the role of genetic variants within genes encoding for collagens of the connective tissue in diverticulosis. DESIGN: This was a transsectional genetic association study. SETTINGS: This study was conducted at three tertiary referral centers in Germany and Lithuania. PATIENTS: Single-nucleotide polymorphisms in COL3A1 ( rs3134646, rs1800255 ) and COL1A1 ( rs1800012 ) were genotyped in 422 patients with diverticulosis and 285 controls of white descent by using TaqMan assays. MAIN OUTCOME MEASURES: The association of colonoscopy-proven diverticulosis with genetic polymorphisms with herniations was assessed in multivariate models. RESULTS: The rs3134646, rs1800255, and rs1800012 variants were significantly associated with the risk of developing diverticulosis in the univariate model; however, these associations were not significant in the multivariate logistic regression analysis including additional nongenetic variables. When selectively analyzing sexes, the genotype AA (AA) in rs3134646 remained significantly associated with diverticulosis in men (OR, 1.82; 95% CI, 1.04–3.20; p = 0.04). LIMITATIONS: Because a candidate approach was used, additional relevant variants could be missed. Within our cohort of patients with diverticulosis, only a small proportion had diverticular disease and thus, we could not examine the variants in these subgroups. Functional studies, including the analysis of the involved collagens, are also warranted. CONCLUSIONS: Our study shows that a variant of COL3A1 ( rs3134646 ) is associated with the risk of developing colonic diverticulosis in white men, whereas rs1800255 ( COL3A1 ) and rs1800012 ( COL1A1 ) were not associated with this condition after adjusting for confounding factors. Our data provide novel valuable insights in the genetic susceptibility to diverticulosis. SeeVideo Abstract athttp://links.lww.com/DCR/A504 .